Farmer-managed irrigation systems in Chitral - Khan, A.H.; Majid, A.; Hussein, M.H.; Vander Velde, E.J. (International Irrigation Management Institute, 1994)
Study of three traditional farmer-developed and -managed irrigation systems in the Chitral region of Pakistan which adds to the existing inventory of information available about indigenous irrigation institutions , technologies, performance, and development needs .